2006
DOI: 10.1007/s00247-006-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of inflammatory bowel disease: a prospective, blinded, comparative study

Abstract: Increased BWT has good positive predictive value for moderate/severe disease in the colon proximal to the rectum (>3 mm), and terminal ileum (>2.5 mm). BWT below this cannot exclude moderate/severe mucosal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 35 publications
1
52
0
2
Order By: Relevance
“…A single bowel wall thickness of 2.5-3 mm or more is considered abnormal and specific for diagnosis of Crohn disease in patients with suspected inflammatory bowel disease (11). Bowel wall thickening may be concentric or eccentric, and the echogenic submucosal layer is often the thickest portion of the bowel wall (Figs 2, 3).…”
Section: Mural Thickeningmentioning
confidence: 99%
See 3 more Smart Citations
“…A single bowel wall thickness of 2.5-3 mm or more is considered abnormal and specific for diagnosis of Crohn disease in patients with suspected inflammatory bowel disease (11). Bowel wall thickening may be concentric or eccentric, and the echogenic submucosal layer is often the thickest portion of the bowel wall (Figs 2, 3).…”
Section: Mural Thickeningmentioning
confidence: 99%
“…When mesenteric venous thrombosis is noted, the liver should be carefully evaluated for abscesses (24). Spectral Doppler US has also been used to assess the mesenteric vasculature in patients with Crohn disease, although some researchers have concluded that spectral Doppler US findings do not reliably correlate with disease activity (11,25).…”
Section: Mesenteric Findings Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra-mural findings include changes involving the surrounding mesentery, that appears thickened and hyperechoic and generally shows enlarged mesenteric lymph-nodes ( Figure 4) [30,36] . Bowel US and ileocolonoscopy with histology have demonstrated an overall sensitivity of 74 and 88% and a specificity of 78 and 93%, respectively, in the detection of SB CD lesions [35,37] . The sensitivity of US in the detection of SB lesions is greater for those of the terminal ileum (approximately 90%-95%) than for those of the proximal SB (75%) [38] .…”
Section: Ultrasonographymentioning
confidence: 99%